2001
DOI: 10.1128/mcb.21.9.2991-3000.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Liver X Receptor-Retinoid X Receptor as an Activator of the Sterol Regulatory Element-Binding Protein 1c Gene Promoter

Abstract: In an attempt to identify transcription factors which activate sterol-regulatory element-binding protein 1c (SREBP-1c) transcription, we screened an expression cDNA library from adipose tissue of SREBP-1 knockout mice using a reporter gene containing the 2.6-kb mouse SREBP-1 gene promoter. We cloned and identified the oxysterol receptors liver X receptor (LXR␣) and LXR␤ as strong activators of the mouse SREBP-1c promoter. Sterol-regulatory element (SRE)-binding proteins (SREBPs) are transcription factors which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
372
3
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(405 citation statements)
references
References 46 publications
24
372
3
6
Order By: Relevance
“…Although it has been reported that supplementation with quercetin as a discrete molecule decreases SREBP1c expression both at the protein and mRNA level in primary rat hepatocytes 30 and in mouse adipocytes 31, our results are consistent with the reported increase in liver X receptor (LXR) α expression and activation by quercetin 32, 33. LXR activation potently upregulates SREBF1c expression 34. Phytochemicals other than quercetin in the dill and kale extracts could have synergistically contributed to LXR activation by sustaining its expression to allow it to upregulate SREBF1c expression.…”
Section: Resultssupporting
confidence: 91%
“…Although it has been reported that supplementation with quercetin as a discrete molecule decreases SREBP1c expression both at the protein and mRNA level in primary rat hepatocytes 30 and in mouse adipocytes 31, our results are consistent with the reported increase in liver X receptor (LXR) α expression and activation by quercetin 32, 33. LXR activation potently upregulates SREBF1c expression 34. Phytochemicals other than quercetin in the dill and kale extracts could have synergistically contributed to LXR activation by sustaining its expression to allow it to upregulate SREBF1c expression.…”
Section: Resultssupporting
confidence: 91%
“…LXR ligands have been shown to activate SREBP-1c expression by inducing binding of LXR to binding sites on the promoter. 48 SREBP-1c has been described as a factor involved in adipocyte differentiation. 49 It has been postulated that deregulation of SREBP controlled gene expression could contribute to cell transformation and tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are key regulators of glucose and lipid metabolism. TR has been shown to regulate the transcription of these genes either through TRE or via response elements identified as LXRE or PPRE (Schoonjans et al, 1996;Jansen et al, 2000;Yoshikawa et al, 2001;Araki et al, 2005;Hashimoto et al, 2009;Gauthier et al, 2010). However, most studies were carried out in vitro.…”
Section: Crosstalk With Other Nuclear Receptorsmentioning
confidence: 99%